Suzie solves the equation below:
x2 + 4x - 12 = 2
(x - 2)(x + 6) = 2,
by setting x -2 = 0 and x + 6 = 0.
Her solutions are x = 2 and x = -6.
Is Suzie correct? Why or why not?

Respuesta :

Answer:

Suzie's answers are incorrect.

Step-by-step explanation:

x^2+4x-12=2

           +12  +12

x^2+4x=14

(if we put Suzie's answer in for x)-

2^2+4(2)=14

4+8=14

Suzie's first answer is incorrect (4+8=12)

Let's try the next one with Suzie's answer

(-6-2)(-6+6)=2

(-8)(0)=2

This answer is also incorrect. (-8*0=0)

ACCESS MORE